CAN CELEBRITY ENDORSE IMPROVE THE PURCHASE DECISION OF “CLOTHING” MSME PRODUCTS THROUGH BRAND IMAGE? - Adelia Rahma; Sudarmiatin; Agus Hermawan; Amelia Setyawati; Farij Ibadil Maula (Badan Penerbit STIEPARI Press, 2022)
The purpose of the study was to determine (1) the description of the celebrity endorse variable, brand image, and purchasing decisions; (2) The direct effect of celebrity endorsement on a brand image; (3) The direct effect of brand image on purchasing decisions (4) The direct influence of celebrity endorsements on purchasing decisions; and (5) the indirect effect of celebrity endorsement on purchasing decisions through the brand image on Awesam Malang Raya customers. This study uses a quantitative approach with descriptive and explanatory research types. The instrument used is a closed questionnaire which is processed in the validity and reliability test with valid and reliable results. The research population is Malang Raya Awesam customers who decide to buy Awesam clothing products. and have seen endorser Selia Rahma. The sampling technique used a proportional random sampling technique. Calculation of the sample using the Slovin formula with a total of 90 respondents. The analysis used is Path Analysis. The prerequisite test is through the normality test with the results of the residuals being normally distributed and the linearity test with the results of the linear path equation. The results showed that the results of the descriptive analysis of celebrity endorsements and purchasing decisions were included in the good category, and the brand image was included in the good category. The results of path analysis show that (1) celebrity endorsement has a direct effect on brand image; (2) brand image has a direct effect on purchasing decisions; (3) celebrity endorsement has a direct effect on purchasing decisions, and (4) celebrity endorse does not indirectly affect purchasing decisions through the brand image on customers of Awesam store Malang Raya.